Improvement of HR processes as a condition of modernization of personnel policy in the health system - A. D. Kaprin; A. A. Kostin; B. T. Ponomarenko; O. V. Gridnev; Yu. V. Samsonov (Исследования и практика в медицине, 2015)
The personnel potential of the Russian health care system has been analyzed. The main issues and trends in the development of our personnel, the dynamics of human processes in health care organizations have been revealed. The correlation of modernization processes with quantitative and qualitative indicators of their personnel has been determined. The role of the personnel policy of the industry in the development of HR processes in the health system has been characterized.